Lung function reduction among welders - Deborah Siregar; Yenni Ferawati (Intelektual Pustaka Media Utama, 2022)
Welding is associated with regular exposure to dust and fumes. Many studies have proven that there is a decrease in lung function due to exposure to this agent. This study aimed to quantitatively analyze the risk factors of impaired lung function among welders in Binong, Tangerang, Indonesia. This was a cross-sectional study design. The lung function of 30 welders is measured by spirometry using the parameters of vital capacity (VC), forced vital capacity (FCV), forced expiratory volume in one second (FEV1), and the ratio of FEV1/FVC. Chi-square analysis was performed and showed that 20 respondents (67%) had impaired lung function, while 10 respondents (33%) had normal lung function. Another factor contributing to impaired lung function among welding workers was their nutritional status, whereby respondents with abnormal nutritional status (body mass index (BMI) 18.4 or ≥25.1) were at 2.15 times higher risk of suffering from impaired lung function compared to respondents with normal nutritional status. Additionally, respondents who did not exercise regularly were at 1.22 times higher risk of impaired lung function compared to those who exercised regularly. Therefore, it is necessary to collaborate with the local community health center to monitor the health of the welders. It is recommended to carry out regular health checks, specifically pulmonary examination, at least once at a year to keep track of the health development of the workers. It is important to equip the workspace with a good ventilation system, and to have the welder work with appropriate personal protective equipment.